DESCRIPTION OF ORDER 3 HYPERGROUPS OVER GROUP ARISING FROM DIHEDRAL GROUP D_9 - Zolfaghary, Parvaneh (Proceedings of the YSU A: Physical and Mathematical Sciences, 2013)
In the present paper we describe, up to isomorphism, all order 3 unitary hypergroups over group, arising from the dihedreal group D_9.